Phytochemical analysis, investigation of antioxidant and anti-inflammatory activities of ethanolic and aqueous extracts of roots of Combretum glutinosum Perr. ex DC from Cote d’Ivoire - Tahiri, Sylla; Fulgence, M’bra Kouassi; Kouame, Dongui Bini (European Journal of Chemistry, 2022)
The phytochemical, antioxidant, and anti-inflammatory potential of root (ethanol and aqueous) extracts of Combretum glutinosum was investigated in this study. Their antioxidant activity was determined using an in vitro DPPH radical scavenging activity assay. The ethanol extract had the lowest IC50 (0.055 mg/mL), which is comparable to vitamin C. Phytochemical screening of extracts revealed the presence of sterols and polyterpenes, polyphenols, alkaloids, flavonoids, catechin tannins, gallic tannins, saponosides, terpenoids, mucilages, anthocyanins, volatile oils, and cardiac glycosides. The extracts significantly inhibit the development of paw edema induced by carrageenan. Anti-inflammatory studies showed that the inflammation inhibition potential of 200 mg/kg body weight of all extracts was significantly lower than the standard diclofenac (20 mg/kg) in the first hours. At the third hour, the inflammation inhibition potential of ethanolic and aqueous extracts was significantly higher than that of the standard. This study revealed that Combretum glutinosum extracts have anti-inflammatory effects and can act as an effective antioxidant.